2020
DOI: 10.1128/jvi.02025-19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HLA-B*52:01-Driven Escape Mutations on Viral Replicative Capacity

Abstract: HLA-B*52:01 is strongly associated with protection against HIV disease progression. However, the mechanisms of HLA-B*52:01-mediated immune control have not been well studied. We here describe a cohort with a majority of HIV C-clade-infected individuals from Delhi, India, where HLA-B*52:01 is highly prevalent (phenotypic frequency, 22.5%). Consistent with studies of other cohorts, expression of HLA-B*52:01 was associated with high absolute CD4 counts and therefore a lack of HIV disease progression. We here exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
1
3
0
3
Order By: Relevance
“…The consensus sequence of Gag280 in the HIV-1 subtype C virus was Val. A recent study demonstrated a reduced viral replication capacity of the subtype C virus having a GagV280T/S/A mutation as compared with that of the consensus-type subtype C virus (33). This present study also showed no significant difference in viral-replication capacity between the subtype B virus (NL4-3)…”
Section: Downloaded Fromsupporting
confidence: 57%
“…The consensus sequence of Gag280 in the HIV-1 subtype C virus was Val. A recent study demonstrated a reduced viral replication capacity of the subtype C virus having a GagV280T/S/A mutation as compared with that of the consensus-type subtype C virus (33). This present study also showed no significant difference in viral-replication capacity between the subtype B virus (NL4-3)…”
Section: Downloaded Fromsupporting
confidence: 57%
“…While there is sequence variation within the epitope, the P2 and P8 anchor positions are highly conserved ( Tables S3 and S4 ) [ 19 ]. HLA-B*52 has been associated with resistance to HIV-1-infection [ 20 ], with early control after infection [ 16 ] and with non-progression to AIDS [ 21 , 22 , 23 , 24 , 25 ]. So far, it has been speculated that this beneficial effect of HLA-B*52 is mediated by CTL selecting escape mutations within HLA B*52-restricted Gag- and Pol-epitopes leading to decreased viral replicative capacity [ 22 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…HLA-B*52 has been associated with resistance to HIV-1-infection [ 20 ], with early control after infection [ 16 ] and with non-progression to AIDS [ 21 , 22 , 23 , 24 , 25 ]. So far, it has been speculated that this beneficial effect of HLA-B*52 is mediated by CTL selecting escape mutations within HLA B*52-restricted Gag- and Pol-epitopes leading to decreased viral replicative capacity [ 22 , 26 ]. Here, we report on the delineation of the Rev-RI8 peptide as a new HLA-B*52-restricted CTL epitope in Rev.…”
Section: Discussionmentioning
confidence: 99%
“…The modest polymorphism observed for topologically important epitopes that precludes them from being classified as exact matches in HIV-1 M group is likely the result of their underlying immunogenicity, which we observed in this study. Moreover, mutations within highly networked epitopes have been shown to impair viral fitness, so these responses may be effective in mediating immune control despite mutational changes [ 26 , [59] , [60] , [61] ]. The finding that the Network epitopes display some sequence variation and were targeted more robustly than the Epigraph peptides could indicate that these are more immunogenic in vivo and that these topologically important regions would indeed be part of the peptide repertoire presented on infected target cells.…”
Section: Discussionmentioning
confidence: 99%